Evolving 50–50% bilingual pedagogy in Alberta: what does the research say? - Naqvi, Rahat; Schmidt, Elaine; Krickhan, Marlene (Frontiers in Psychology, 2014)
This paper outlines the provincial frameworks that define the Spanish bilingual program in Alberta, Canada, provides an historical overview of its pedagogic constraints and evolution, and proposes a framework for bilingual pedagogy. The framework is conceptualized from the research evidence of three local case studies, and is based on the centrality of cross-linguistic transfer, in relation to linguistic interdependence and bilingual learning.